2023
DOI: 10.3390/ma16072830
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Exact Effects of Various Factors on Chloride Diffusion in Cracked Concrete: ABAQUS-Based Mesoscale Simulations

Abstract: Chloride ion attack is a major cause of concrete durability problems, and existing studies have rarely addressed the effects of damage zones. In this paper, an improved mesoscale model including five phases was constructed using the finite element software ABAQUS to study the diffusivity of chloride ions in cracked concrete. It was found that the damage zone is negligible when the crack width is less than 50 μm, while the width and depth of the damage zone are about 15 times the crack width and 15% of the crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…The crack is located at the midpoint of the left boundary of the concrete, running parallel to the upper and lower boundaries and penetrating into the interior of the concrete. In the four-phase model, aggregates are assumed to be circular, and according to previous studies, the shape of aggregates has a minimal impact on chloride ion diffusion in concrete [31,32]. The Walraven formula [33] is used to generate aggregates with diameters ranging from 5 mm to 15 mm, with a volume percentage of 50%.…”
Section: Disadvantagesmentioning
confidence: 99%
“…The crack is located at the midpoint of the left boundary of the concrete, running parallel to the upper and lower boundaries and penetrating into the interior of the concrete. In the four-phase model, aggregates are assumed to be circular, and according to previous studies, the shape of aggregates has a minimal impact on chloride ion diffusion in concrete [31,32]. The Walraven formula [33] is used to generate aggregates with diameters ranging from 5 mm to 15 mm, with a volume percentage of 50%.…”
Section: Disadvantagesmentioning
confidence: 99%
“…During the review of the pertinent articles, researchers discovered that they had used binders, including fly ash, glass powder, lime, coal ash, and cow dung powder, among others. It was observed that the use of all of these binders positively impacted the water absorption characteristics of the CSEBs and effectively subdued the block's maximum water absorption capacity [85,86]. The results were more pronounced when the cement and fly ash were used as binders to stabilize the earth blocks.…”
Section: Water Absorptionmentioning
confidence: 99%